2022
DOI: 10.1007/s00018-022-04410-2
|View full text |Cite|
|
Sign up to set email alerts
|

Single-cell RNA-sequencing of zebrafish hair cells reveals novel genes potentially involved in hearing loss

Abstract: Hair cells play key roles in hearing and balance, and hair cell loss would result in hearing loss or vestibular dysfunction. Cellular and molecular research in hair cell biology provide us a better understanding of hearing and deafness. Zebra sh, owing to their hair cell-enriched organs, have been widely applied in hair cell-related research worldwide. Similar to mammals, zebra sh have inner ear hair cells. In addition, they also have lateral line neuromast hair cells. These different hair cells vary in morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…These molecular signatures are conserved across larval and adult stages. However, consistent with other recent work ( Jimenez et al, 2022 ; Qian et al, 2022 ), we were not able to resolve distinct clusters of hair cells or supporting cells corresponding to the distinct types of maculae: i.e. utricle, saccule, and lagena.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These molecular signatures are conserved across larval and adult stages. However, consistent with other recent work ( Jimenez et al, 2022 ; Qian et al, 2022 ), we were not able to resolve distinct clusters of hair cells or supporting cells corresponding to the distinct types of maculae: i.e. utricle, saccule, and lagena.…”
Section: Discussionsupporting
confidence: 85%
“…Recent single-cell and single-nucleus RNA-sequencing efforts have generated a wealth of transcriptomic data from hair cells in several model systems, facilitating more direct comparison of cell types and gene regulatory networks between species. Although single-cell transcriptomic data have recently been published for the zebrafish inner ear ( Jimenez et al, 2022 ; Qian et al, 2022 ), the diversity of hair cell and supporting cell subtypes has not been thoroughly analyzed. In order to better understand the diversification of cell types in the zebrafish inner ear, and their relationships to those in mammals, here we perform single-cell and single-nucleus RNA sequencing of the zebrafish inner ear from embryonic through adult stages.…”
Section: Introductionmentioning
confidence: 99%
“…S7G). Consequently, we conducted a cross-species comparison between the HCLC cluster to hair cell–related tissues in zebrafish ( 39 ). The results indicated that the HCLC cluster in zone 3 exhibits a high similarity with hair cell populations and hair cell progenitors of the acoustico-lateralis system in zebrafish (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the similarity between the endostyle cell types and vertebrate tissues, we collected scRNA-seq data of zebrafish from Farnsworth et al ( 30 ), Qian et al ( 39 ), and Gillotay et al ( 40 ) as reference datasets. Before comparing the endostyle and zebrafish tissues, we preprocess the zebrafish datasets to unify the annotations and eliminate batch effects between different samples.…”
Section: Methodsmentioning
confidence: 99%
“…Recent single-cell and single-nucleus RNA-sequencing efforts have generated a wealth of transcriptomic data from hair cells in several model systems, facilitating more direct comparison of cell types and gene regulatory networks between species. Although single-cell transcriptomic data have recently been published for the zebrafish inner ear (Jimenez et al, 2022;Qian et al, 2022), the diversity of hair cell and supporting cell subtypes has not been thoroughly analyzed.…”
Section: Introductionmentioning
confidence: 99%